Fault diagnosis scheme for open‐circuit faults in switched reluctance motor drives using fast Fourier transform algorithm with bus current detection. Issue 1 (1st January 2016) - Gan, Chun; Wu, Jianhua; Yang, Shiyou; Hu, Yihua; Cao, Wenping; Si, Jikai
Abstract : Reliability of power converters is of crucial importance in switched reluctance motor drives used for safety‐critical applications. Open‐circuit faults in power converters will cause the motor to run in unbalanced states, and if left untreated, they will lead to damage to the motor and power modules, and even cause a catastrophic failure of the whole drive system. This study is focused on using a single current sensor to detect open‐circuit faults accurately. An asymmetrical half‐bridge converter is considered in this study and the faults of single‐phase open and two‐phase open are analysed. Three different bus positions are defined. On the basis of a fast Fourier transform algorithm with Blackman window interpolation, the bus current spectrums before and after open‐circuit faults are analysed in details. Their fault characteristics are extracted accurately by the normalisations of the phase fundamental frequency component and double phase fundamental frequency component, and the fault characteristics of the three bus detection schemes are also compared. The open‐circuit faults can be located by finding the relationship between the bus current and rotor position. The effectiveness of the proposed diagnosis method is validated by the simulation results and experimental tests.